English for international tourism : intermediate students' book. - Strutt, Peter, ....- (Essex : Longman, 2003)
English for International Tourism provides a multi-level series for students who need professional communication within the hotel and tourism industries. Explores top tourist destinations using material taken from Dorling Kindersleys Eyewitness Travel Guides Brings the world of work into the classroom Provides effective communication strategies for workplace situations Develops language awareness through an integrated syllabus
Keywords: Engels -- Toerisme; Go international; International office